ANALISIS PERAN PEMERINTAH DESA DALAM PENYUSUNAN ANGGARAN DANA DESA UNTUK PENGEMBANGAN PROGRAM KESEHATAN DI POSYANDU KECAMATAN SRENGAT KABUPATEN BLITAR - Linda Ismawati; Ayun Sriatmi; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Since 2015 source of village income increased, it was because getting allocations from the central government called (the village fund). However, the budgetary funds provided for Posyandu as one of the basic services in the village center was still low, while there are many health problems that occur. This is possible because of the lack of concern for the government in improving the utilization of the village fund for Posyandu. This study aims to determined the government’s role in the preparation of the budget for the development of health programs in the Posyandu. This study used a qualitative method by which data were obtained from 4 (four)- depth interviews with the village chief. The results showed that interpersonal’s role in participation and evaluation budgetary had not been good. This is indicated by the exclusion of Posyandu cadres in the preparation of the budget in one of the villages and the lack of coordination in evaluating the budget in several villages. The village chief related to informational’s role in the preparation of the budget was also not optimal, it was indicated by the complaints of cadres in Posyandu who felt the village chief did not find out about the clarity of targets, difficulty of targets, and evaluation of the existing budget in Posyandu. In a decisional’s role was also not going optimally, as indicated by the complains of the secretary of the village who said in decision-making related to difficulty of targets and evaluation of budgets submitted to him. Where the village chief should also be required to had decision making skills in solving problems that exist within the organization he leads. This is expected village chief can improve coordination and good communication both with the village secretary and cadres in order to avoid misunderstandings and differences of perception related to the budget given to Posyandu.